Meningkatkan Kapasitas Perangkat Desa dengan Memberikan Pelatihan Public Speaking di Margaluyu, Kota Serang - Eka Susilawati; Noerma Kurnia Fajarwati; Sindy Pramudita; Ismi Latifah; Nadivah Nadivah (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The ability to speak in public is an important competency required by village officials in carrying out leadership duties, communicating with the community, and delivering village development programs. This service program aims to increase the capacity of village officials in Margaluyu Village, Serang City, through public speaking skills training. This training is designed with a practical approach which includes communication theory, persuasion techniques, and simulations of speaking in front of an audience. Through this training, village officials are expected to be able to communicate more effectively, increase self-confidence, and strengthen community participation in various village activities. The evaluation results showed that after the training, participants experienced improvements in communication skills, message preparation, and how to interact with residents. It is hoped that this program can become a model for improving the quality of human resources in other villages.